Formulation and evaluation of hydroxyzine hydrochloride sustained release microspheres by ionotropic gelation technique using Carbopol 934P - Ghosh, Mr. Soumyadeep (Asian Journal of Pharmaceutics (AJP), 2014)
Preparation of sustained release microspheres of hydroxyzine hydrochloride by ionotropic gelation technique and evaluation. Microspheres of hydroxyzine hydrochloride were prepared by ionotropic gelation method using sodiumÂ alginate, Carbopol 934P and calcium chloride. The powders were evaluated for their flow properties. HydroxyzineÂ hydrochloride microspheres were characterized by Fourier transform infrared and in vitro dissolution studies. The drugÂ release study of hydroxyzine hydrochloride microspheres was evaluated using basket type dissolution test apparatus. TheÂ release rate of Hydroxyzine hydrochloride microspheres was studied for 12 h in pH 7.4 phosphate buffer media. From theÂ five batches F5 batch showed good release behavior 91.08% of drug is released over 12 h, and r2 = 0.987 in zeroâ€orderÂ kinetics. The microspheres were prepared without the use of organic solvents. Microspheres of hydroxyzine hydrochlorideÂ decrease the incidence of side effects and also improve patient compliance by reducing the number of dosing and by reducingÂ the fluctuations of drug in the blood. This entire attributed attitude proves that microsphere technology from novel drugÂ delivery can be very much effective in reducing dosage frequency, dose dumping, and better patient compliance and economical to the patient. In the future, natural, biodegradable polymers can be used to improve therapeutic efficacy of the drug and further minimizing sideâ€effects. Key words: Carbopol 934P, hydroxyzine hydrochloride, ionotropic gelation technique, microspheres, sodium alginate